2018
DOI: 10.1002/cbin.11073
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic stability of the human MG‐63 osteoblastic cell line at different passages

Abstract: One of the most popular cell lines in osteogenesis studies is the human osteoblastic line MG-63. For cell biological investigation, it is important that the cells remain stable in their phenotype over several passages in cell culture. MG-63 cells can be used to provide fundamental insights into cell--material interaction. The aim of this study is to present a systematic characterization of the physiological behavior of MG-63 cells in the range of passages 5-30. Significant cell physiology processes during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…Some studies showed different cell line stabilities in cell phenotype and functional characteristics from P10 up to P30, regarding (54,55) and genomic stability from P5 to P13 (52,53,56). We used cells in a lower passage based on a previous literature that described genomic stability in lower passages and the use of all cells in a similar passage for experimental homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed different cell line stabilities in cell phenotype and functional characteristics from P10 up to P30, regarding (54,55) and genomic stability from P5 to P13 (52,53,56). We used cells in a lower passage based on a previous literature that described genomic stability in lower passages and the use of all cells in a similar passage for experimental homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured in Dulbecco's Modified Eagle Medium (DMEM, 31966-021, Life Technologies Limited, Paisley, United Kingdom), with 10% fetal calf serum (FCS, Biochrom FCS Superior, Merck, Darmstadt, Germany) and 1% antibiotics (gentamicin, Ratiopharm, Ulm, Germany) at 37 • C with 5% CO 2 /95% air atmosphere (Staehlke et al, 2018). All experiments were performed in passages 5-30, as the MG-63 cell physiology is known to remain stable over the entire range of these passages (Staehlke et al, 2019).…”
Section: Cell Culturementioning
confidence: 99%
“…Surface charges can generate electrical cues necessary to regulate cell function (De Aza et al, 2003;Finke et al, 2007;Fernández-Yagüe et al, 2019). As human osteoblasts are negatively charged (Rebl et al, 2016), positive surface charges significantly influence cell adhesion (Rebl et al, 2010;Dhowre et al, 2015;Mörke et al, 2017), spreading and proliferation (Staehlke et al, 2019), particularly in the early stages of cell responses. The most detailed study on the effect of surface charges to date is that of Metwally and Stachewicz (2019), indicating a great importance in the development of functionally implantable biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The surfaces of biomaterials play a central role in the modulation of cell behavior [42,43] and in mechanotransduction [7,44,45]. Topographical features have an influence on direct transmission of force, which causes a reorganization of the cytoskeleton [31,[46][47][48] and changes in cell shape to adapt to the underlying surface [44,49,50]. Furthermore, signaling pathways ultimately modulate cell proliferation and differentiation [4,5,8,10,46,[51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblast-like human cells MG-63 (American Type Culture Collection, ATCC ® CRL-1427 ™ ), Manassas, VA, USA) were cultured in Dulbecco's modified Eagle's medium (DMEM, Life technologies GmbH, Darmstadt, Germany) with 10% standardized fetal calf serum (FCS, Biochrom FBS Superior, EU-approved, Merck KgaG, Darmstadt, Germany) and 1% gentamycin (Ratiopharm GmbH, Ulm, Germany) (complete media) at 37 • C in 5% CO 2 according to the protocols described previously [9,13,31]. The experiments were carried out at a cell confluence of~70%.…”
Section: Cell Culture and Subcellular Fractionationmentioning
confidence: 99%